A COMPARATIVE STUDY OF MANUAL REDUCTION AND OVARIOHYSTERECTOMY IN POSTPARTUM UTERINE PROLAPSE OF DOMESTIC CATS - S. Sathishkumar; S. Rangasamy; J. Umamageswari; R. Sureshkumar; D. Reena; K. Krishnakumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Uterine prolapse in cats of twelve clinical cases brought to the Madras Veterinary College Teaching Hospital with a history of cats queened recently, severe straining, anorexia, pyrexia and round red swollen edematous mass protruding through the vulva were used for the present study. Based on the clinical examination, the cases were diagnosed as uterine prolapse either unilateral or bilateral horns. Ovariohysterectomy (n=6) was performed in six delayed cases and manual reduction (n=6) was done in six fresh cases. Cats that underwent surgery recovered uneventfully after one week of postoperative management. Manually reduced cases also recovered after one week of medical management.